The influence of gratitude journalling on the motivation and English language proficiency of young adult isiXhosa speakers - Aspeling, Lara Lee (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (General Linguistics))--University of Stellenbosch, 2011.